Variation of the Side Chain Branch Position Leads to Vastly Improved Molecular Weight and OPV Performance in 4,8-dialkoxybenzo[1,2-b:4,5-b′]dithiophene/2,1,3-benzothiadiazole Copolymers - Robert C. Coffin; Christopher M. MacNeill; Eric D. Peterson; Jeremy W. Ward; Jack W. Owen; Claire A. McLellan; Gregory M. Smith; Ronald E. Noftle; Oana D. Jurchescu; David L. Carroll (Journal of Nanotechnology)
Through manipulation of the solubilizing side chains, we were able to dramatically improve the molecular weight (Mw) of 4,8-dialkoxybenzo[1,2-b:4,5-b′]dithiophene (BDT)/2,1,3-benzothiadiazole (BT) copolymers. When dodecyl side chains (P1) are employed at the 4- and 8-positions of the BDT unit, we obtain a chloroform-soluble copolymer fraction with Mw of 6.3 kg/mol. Surprisingly, by moving to the commonly employed 2-ethylhexyl branch (P2), Mw decreases to 3.4 kg/mol. This is despite numerous reports that this side chain increases solubility and Mw. By moving the ethyl branch in one position relative to the polymer backbone (1-ethylhexyl, P3), Mw is dramatically increased to 68.8 kg/mol. As a result of this Mw increase, the shape of the absorption profile is dramatically altered, with λmax = 637 nm compared with 598 nm for P1 and 579 nm for P2. The hole mobility as determined by thin film transistor (TFT) measurements is improved from ~1×10−6 cm2/Vs for P1 and P2 to 7×10−4 cm2/Vs for P3, while solar cell power conversion efficiency in increased to 2.91% for P3 relative to 0.31% and 0.19% for P1 and P2, respectively.